Patient management with imperfect amelogenesis - Vargas-Machuca, Mónica, Valdivieso (2020)
Amelogénesis imperfecta (AI) is an inherited disorder that affects enamel, characterized by hypomineralization or hypoplasia with discoloration, sensitivity and fragility. Report an uncooperative female patient aged five is taken to the emergency Cayetano Heredia Dental Clinic because of pain. During the anamnesis the parent revealed his second son had the same condition as his younger daughter.Clinical and radiographic evaluation the patient presented: multiple cavitated lesions, necrotic pulp and enamel hypoplasia. Through these tests a presumptive diagnosis enamel defect: Amelogenesis Imperfecta was reached. The clinic advised the parent of the various treatment available, the parent opted for a comprehensive treatment under general anesthesia; having extracted the workpiece 75, aspartame ́s of the treatment, The extracted tooth was taken to pathology services for analysis. Diagnosis: Amelogenesis imperfecta hypoplastic.Treatment plan: prophylaxis and application of fluoride varnish c / 2 months, pulpectomy installation steel crowns and preformed, resin restorations. Discussion It is important to find out whether family members show the same tooth disorder (hereditary malformation). When the diagnosis is confirmed AI should be considered early as a comprehensive treatment. The lifetime decreased direct restorations in patients with AI, suggests a constant maintenance of restorations until final prosthetic restorations can be made. In the case of large destructions of primary teeth, they are indicated stainless steel crowns.Conclusions: The AI is a hereditary disorder that must be diagnosed at an early stage and be treated comprehensively with frequent periodic checks. The use of preformed steel crowns for posterior teeth and resins for anterior teeth could be the best alternatives in patients with AI